The Dynamics of Protecting Women with Disabilities in West Sumatra, from Socio-Cultural Pressure to Policy Advocacy - Soraya Oktarina (Journal of Feminism and Gender Studies, 2025)
Social justice for all Indonesian people is a mandate of the 5th principle of Pancasila which must be implemented, without distinguishing between certain types of groups. People with disabilities, a minority group who have equal rights in various aspects of life. Efforts to guarantee a decent life for people with disabilities are still homework that continues to be pursued, but not much is focused on gender with disabilities. Apart from having to accept the condition of being disabled, women with disabilities are often hit with negative stigma which leads to threats of gender violence, not only in the private, public and even structural spheres, which has an impact on women being left behind in various areas of life and leading to violations of human rights. In West Sumatra, violence against women with disabilities is still quite high, with the majority of cases resolved without bias towards the victim. This research uses descriptive qualitative methods. The aim of this research is to look at the problems experienced by women with disabilities in West Sumatra and the protection efforts taken. The research results show that West Sumatra continues to strive to fulfill the guarantee of protection for women with disabilities with various regulations and the availability of institutions, but in terms of implementation, violence against women with disabilities is still high. Socio-cultural pressures and dead-end advocacy efforts are a problem. Weak evidence, power relations, and a "one-sided" view of women with disabilities are the main factors.  An inclusive approach is needed from various sectors by increasing awareness, accessibility, involvement and support for people with disabilities.